Evolutionary histories and antimicrobial resistance in Shigella flexneri and Shigella sonnei in Southeast Asia - Hao Chung The (Nature Portfolio, 2021)
Hao Chung The et al. analyze 1,804 Shigella genome sequences from organisms isolated in four Southeast Asian countries over three decades to study the evolution of both S. flexneri and S. sonnei. This study suggests that adaptation to antimicrobial pressure may have played a pivotal role in the recent evolutionary trajectory of Shigella in Southeast Asia.